Healthcare-associated Infections by Pseudomonas aeruginosa and Antimicrobial Resistance in a Public Hospital from Alagoas (Brazil) - Maria Anilda dos Santos Araújo; Joiciane Santos Rodrigues; Teresa de Lisieux Guedes Ferreira Lobo; Fernanda Cristina de Albuquerque Maranhão (Sociedade Brasileira de Patologia Clínica, 2022)
ABSTRACT Introduction Pseudomonas aeruginosa infections are common worldwide, affecting mainly hospitalized patients and causing healthcare-associated infections (HAIs), with a high frequency of antibiotic resistance and complicated outcomes. Objective To investigate the P. aeruginosa frequency in HAIs in a medium/high-complexity hospital in Alagoas (Brazil) and the antibiotic susceptibility profiles of the strains. Methods A retrospective cross-sectional study was conducted from January 2013 to December 2014, when P. aeruginosa related-HAIs were evaluated after automated identification (Vitek®2) and documental analysis. Results Seventy-eight samples were positive for P. aeruginosa, with 37 (47.4%) isolates from patients of the general Intensive Care Unit (ICU) and 13 (16.7%) from the surgical unit. Tracheal secretion (25.6%), wound secretions (20.5%) and sputum (18.0%) were the main positive biological samples. Among 68 strains tested, 73.53% showed resistance to aztreonam, while cefepime, ceftriaxone and cefotaxime were not effective for any isolates (all resistant). High resistance to carbapenems imipenem (61.76%) and meropenem (55.88%) was observed, as well as 46 isolates resistant to piperacillin/tazobactam (67.64%); 47 (60.2%) from the general ICU and neonatal ICU were resistant to all antibiotics tested (MDR profile), except for colistin. Conclusion Our results indicated antibiotic-resistant P. aeruginosa highly present in ICU and the therapy with aminoglycosides and colistin as important choices in cases with failure against P. aeruginosa isolates. A constant screening of multidrug-resistant P. aeruginosa is necessary for the control in the hospital environment, evaluating the antibiotic susceptibility to guide the therapeutic choice.